The Implementation of Character Education on the Discipline of Santri - Lailiyah, Nurul; Mukhlisin, Mukhlisin (STAI Miftahul Ula Nganjuk, 2023)
Education is a fundamental component of human development, not limited to the transfer of knowledge from teachers to students, but also serving as a means to shape the character and personality of learners. In this regard, character education plays a pivotal role and must be carried out in a continuous, consistent, and integrated manner across all aspects of school life. This study aims to explore the implementation of character education at Pondok Modern Al-Barokah by employing a qualitative field research approach. Data were collected through observation, interviews, and documentation, and analyzed using a descriptive method. Both deductive and inductive reasoning were utilized to interpret qualitative data and derive meaningful insights. The findings reveal that character education at Pondok Modern Al-Barokah is realized through various strategic approaches. These include exemplary behavior by educators and caregivers (modeling), the creation of a disciplined and value-based environment, structured guidance and coaching, practical training activities, task assignments, and consistent supervision. All of these efforts are integrated into a holistic educational system that operates continuously throughout the day. The unique pesantren environment ensures that every aspect of students’ daily lives—what they see, hear, experience, and practice within 24 hours—contributes to character formation. Thus, character education in this context is not confined to formal classroom instruction but permeates all interactions and experiences in the boarding school. The comprehensive and immersive nature of this educational model underscores its effectiveness in nurturing morally grounded, disciplined, and socially responsible individuals